Effect of fertilizer type and nodal pinching on growth, flowering pattern and yield of cucumber (Cucumis sativus) - Frimpong, Joana (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Olericulture, 2011